2013
DOI: 10.1134/s1068162013040109
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the pseudogene PTENP1 5′-terminal region in endometrial cancer and hyperplasia

Abstract: Genetic mutations in tumor suppressor gene PTEN are often detected in malignant human cells and these genomic changes are especially characteristic ofendometrial cancer. In our previous researches we assumed that alternative epigenetic mechanism of PTEN inactivation trough promoter methylation may exist in endometrial cancer. Moreover, PTENP1 pseudogene has recently been shown to play a role in positive regulation of PTENgene expression. Taking into account these facts, we analyzed PTEN and PTENP1 methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…For instance, Du et al (2019) revealed that DUXAP8 upregulation in colorectal cancer was induced by STAT3; SIX2 played a positive role in CYP4Z2P expression in breast cancer . Some studies demonstrated that the methylation level of pseudogenes linked to the alteration of pseudogene-derived lncRNAs' expression (Kovalenko et al, 2013(Kovalenko et al, , 2018. Hormone and hormone receptor correlated with mis-regulation of pseudogene-derived lncRNAs.…”
Section: Potential Dysregulated Mechanisms Of Pseudogene-derived Lncrmentioning
confidence: 99%
“…For instance, Du et al (2019) revealed that DUXAP8 upregulation in colorectal cancer was induced by STAT3; SIX2 played a positive role in CYP4Z2P expression in breast cancer . Some studies demonstrated that the methylation level of pseudogenes linked to the alteration of pseudogene-derived lncRNAs' expression (Kovalenko et al, 2013(Kovalenko et al, , 2018. Hormone and hormone receptor correlated with mis-regulation of pseudogene-derived lncRNAs.…”
Section: Potential Dysregulated Mechanisms Of Pseudogene-derived Lncrmentioning
confidence: 99%
“…The sample sizes of these studies ranged from 19–155 (median 88). Fourteen studies evaluated the diagnostic value of methylation of a single gene (Sasaki et al, 2001(1) [ 10 ]; Sasaki et al, 2001(2) [ 11 ]; Saito et al, 2003 [ 12 ]; Sasaki et al, 2003 [ 13 ]; Li et al, 2005 [ 14 ]; Pijnenborg et al, 2007 [ 17 ]; Yanokura et al, 2007 [ 18 ]; Tse et al, 2009 [ 20 ]; Varley et al, 2009 [ 21 ]; Yi et al, 2011 [ 22 ]; Kovalenko et al, 2013 [ 25 ]; Yang et al, 2013 [ 27 ]; Chmelarova et al, 2014 [ 28 ]; Dong et al, 2015 [ 30 ]), five studies evaluated multiple genes (Banno et al, 2006 [ 15 ]; Suehiro et al, 2008 [ 19 ]; Fiolka et al, 2013 [ 24 ]; Visnovsky et al, 2013 [ 26 ]; Sheng et al, 2016 [ 31 ]), and the other three studies evaluated both single and combined genes (Shih et al, 2006 [ 16 ]; Zhang et al, 2011 [ 23 ]; Chen et al, 2015 [ 29 ]). Seventeen studies measured the methylation patterns of the genes using methylation-specific polymerase chain reaction (MSP), three studies used combined bisulfite restriction analysis (COBRA), one used quantitative MSP (qMSP), and one used MSP and COBRA for two genes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of PTENP1 expression in liver cancer cells are significantly lower than those in normal hepatocytes. When PTENP1 is overexpressed in liver cancer cells, it helps to modulate the PI3K/AKT signaling pathway, leading to the suppression of cancer cell proliferation, migration, and invasion, resulting in cell autophagy and apoptosis 20. However, little is known about the role of PTENP1 in suppressing glioma cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%